A comparison of experimental time-secondary dendritic spacing and coarsening models for Al-Si-Cu alloys. (June 2020) - Donadoni, Bruno; de Gouveia, Guilherme Lisboa; Garcia, Amauri; Spinelli, José Eduardo
Abstract: Most of the secondary dendrite arm spacing (λ2 ) growth models existing in the literature deal with predictions for binary aluminum (Al) alloys. Only two solutions are available to estimate λ2 for chemistries of major alloying elements in Al alloys, such as copper (Cu) and Silicon (Si). The coarsening models developed by Rappaz-Boettinger and Tiryakioglu were employed in this investigation. The multicomponent models enabled very distinct matches with the experimental data of Al-9 and 11 wt.% Si-3.0 wt.% Cu alloys.